Ignacio Álvarez-Osorio e Ignacio Gutiérrez de Terán. 2022. Qatar. La perla del Golfo. Madrid: Península. 230 pp. ISBN 9788411001106 - Camacho Padilla, Fernando (Estudios de Asia y África, 2023)
Ignacio Álvarez-Osorio e Ignacio Gutiérrez de Terán. 2022. Qatar. La perla del Golfo. Madrid: Península. 230 pp. ISBN 9788411001106